The Regional Impact Of Land-use Change: Social, Economic and Political Environment in Central Sulawesi Indonesia - Hasbullah, Hasbullah; Hasanuddin, Hasanuddin; Palawa, Muhammad Riswandi; Haidir, Haidir; Samad, Muhammad Ahsan; Astuty, Astuty (Technium Social Sciences Journal, 2021)
The aim of this research was to examine and determine the role of the social, economic, and political environments in preventing paddy field conversion in Sigi Regency. The research method used is qualitative, with the methodology of purposefully choosing research informants from the various stakeholders concerned, including the Legislative Institution, rice field owners, community leaders, and housing developers. Furthermore, the implementation model used is an integrative model, which is a combination of several expert-developed implementation models that include social, economic, and political factors. According to the findings of the report, the social, economic, and political climate in Sigi Regency has been supportive of the prohibition on the conversion of paddy fields to other land uses. This can be seen in the Legislature's willingness to issue regulations on the Protection of Sustainable Food Agricultural Land as a representative of political institutions, as well as the need to make special rules prohibiting the conversion of paddy fields once the new Spatial Planning law, which is currently under consideration, is completed. Aside from that, the Legislature would help the budget process and perform oversight functions. Rice field owners and community leaders, as well as housing developers, have praised the legislative support for enforcing rules, budgeting, and monitoring in the light of the efficacy of the policy prohibiting the conversion of paddy fields in Sigi Regency..